ESPEN practical guideline: Clinical Nutrition in cancer. Issue 5 (May 2021) - Muscaritoli, Maurizio; Arends, Jann; Bachmann, Patrick; Baracos, Vickie; Barthelemy, Nicole; Bertz, Hartmut; Bozzetti, Federico; Hütterer, Elisabeth; Isenring, Elizabeth; Kaasa, Stein; Krznaric, Zeljko; Laird, Barry; et al.
Summary: Background: This practical guideline is based on the current scientific ESPEN guidelines on nutrition in cancer patients. Methods: ESPEN guidelines have been shortened and transformed into flow charts for easier use in clinical practice. The practical guideline is dedicated to all professionals including physicians, dieticians, nutritionists and nurses working with patients with cancer. Results: A total of 43 recommendations are presented with short commentaries for the nutritional and metabolic management of patients with neoplastic diseases. The disease-related recommendations are preceded by general recommendations on the diagnostics of nutritional status in cancer patients. Conclusion: This practical guideline gives guidance to health care providers involved in the management of cancer patients to offer optimal nutritional care.